(untitled) (Comprehensive Journal of Science, 2025)
This study was conducted on mung bean samples to evaluate their physical properties and proximate chemical composition. The study aimed to investigate the impact of various processing treatmentsspecifically soaking, roasting, conventional cooking, and pressure cookingon the chemical composition of mung beans.Physical analysis revealed that the average 100-seed weight was 3.89 g, the average 100-seed volume was 3.53 cm³, and the mean seed density was 1.10 g/cm³. The water absorption and swelling rates increased by approximately 100% during a soaking period of 12 to 18 hours.The proximate composition of raw (unprocessed) mung bean seeds was as follows: 7.75% moisture, 26.28% protein, 1.55% fat, 4.10% ash, 3.13% fiber, and 64.94% carbohydrates. In the samples treated, the protein content ranged from 25.11% to 28.08%, fat from 1.38% to 1.53%, ash from 3.35% to 3.88%, and fiber from 2.33% to 3.21%. The carbohydrate content was 67.40%.Except for roasting, all processing treatments led to a significant reduction in the levels of sodium, calcium, potassium, and zinc. The loss in calcium reached 39%, while the loss for iron and copper was approximately 25%. Processing also affected the amino acid profile: the contents of valine, lysine, leucine, isoleucine, cysteine, and tryptophan decreased. However, tyrosine, threonine, and histidine levels decreased with soaking but increased with the other treatments. Phenylalanine content reduced after soaking but was unaffected by other methods, while methionine remained unchanged by all treatments.The protein solubility index was higher in a saline solution compared to water. Roasting, conventional cooking, and pressure-cooking reduced protein solubility, a change attributed to heat-induced protein denaturation.Lastly, all processing treatments except roasting decreased the total soluble sugar content, likely due to leaching into the water. A slight reduction in starch content was also observed across the treatments.